Community Empowerment With Marketing Training By Smart Indonesia Academy To Radar Malang Online - Tanti Widia Nurdiani (International Journal Of Community Service, 2022)
The Industrial Revolution 4.0 is a revolution based on the Malang Online Cyber Physical System Radar, making the media industry increasingly have its own challenges in terms of facing competition for marketing and finding customers. Radar Malang Online, as one of the largest media companies in Malang Raya with a readership rate of more than 200,000 per day, still needs marketing training to increase awareness in the community, especially through the design of promotional media. This study uses qualitative research with an analytical descriptive method. Researchers use primary data, namely interviews, and secondary data, namely journal articles, books, news articles, reports, etc. This literature review uses the theories of community empowerment and marketing training. The activity has been carried out by Smart Indonesia Academy as a form of community empowerment that aims to increase the ability and understanding related to marketing for the Radar Malang Online team. The findings show that the activities carried out by Smart Indonesia Academy as a form of community empowerment aimed at providing innovative and creative efforts with knowledge, insight, and solutions through marketing training to the Radar Malang Online team have been going well. The training provided by Smart Indonesia Academy to improve the performance and motivation of the Radar Malang Online team was in accordance with the understanding related to marketing training.